Technologies applied in the care of patients with Alzheimer's disease - a systematic review - Machado, Savanna Denega; Barbosa, Jorge Luis Victória (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2020)
About 50 million people around the world have Alzheimer's disease. The main characteristic of the disease is the deterioration of cognitive function, and as a result of the fact that the disease has no cure or treatment. This article presents a systematic mapping of the literature to identify articles that use technological devices to assist patients with Alzheimer's disease, in order to show an overview of the literature, identifying gaps and research opportunities. The systematic mapping study was conducted out in six databases, including articles from January 2015 to July 2020. An initial search resulted in 12,177 articles, of which 28 were selected after applying the filter criteria. The main results obtained are: (1) most articles (25.71%, 7/28) reported solutions used in devices with sensor development; (2) most technologies (22.06%, 6/28) were focused on monitoring; (3) most papers (82.14%, 23/28) address solutions for dementia, citing Alzheimer's disease indirectly; (4) more than half of the studies aimed at monitoring patients (54%, 15/28); (5) most studies (82.14%, 23/28) performed an experiment with patients with the disease. The results corroborate the need for technological devices to help caregivers monitor patients, in addition to evidence of research opportunities in palliative care and support for daily activities.